1986
DOI: 10.1038/bjc.1986.235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of adriamycin-induced histamine release in vitro limit adriamycin cardiotoxicity in vivo

Abstract: The activity of theophylline and disodium cromoglycate was tested on adriamycin-induced histamine release in vitro and on adriamycin cardiotoxicity in vivo. Both substances significantly inhibited the release of histamine induced by 100 micrograms ml-1 of adriamycin on rat peritoneal cells and produced significant protection against adriamycin-mediated acute and chronic cardiotoxicity in mice. N-acetylcysteine, a free radical scavenger, successfully used in the prevention of the cardiomyopathy, was also found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…We found that our treatments decreased the histamine level as compared to CP and control groups. Previous studies explain that by suppressing compound 48/80 induced rat peritoneal mast cell degranulation and histamine release [55][56][57].…”
Section: Discussionmentioning
confidence: 95%
“…We found that our treatments decreased the histamine level as compared to CP and control groups. Previous studies explain that by suppressing compound 48/80 induced rat peritoneal mast cell degranulation and histamine release [55][56][57].…”
Section: Discussionmentioning
confidence: 95%
“…Adriamycin-associated arrhythmias have also been documented in case reports and include nonspecific T wave and ST changes and rarely sudden death (8,20). The mechanisms by which adriamycin induces cardiotoxicity have been proposed to include formation of free radicals (19), inhibition of nucleic acid and protein synthesis (4,45), lipid peroxidation (29,35,39), abnormalities in mitochondria (11), lysosomal changes (39), modifications of sarcolemmal Ca 2ϩ transport, diminished activity of adenylate cyclase, Na ϩ -K ϩ -ATPase, and Ca 2ϩ -ATPase activities (11,35,37,38), and the release of histamines and catecholamines (3,22).…”
mentioning
confidence: 99%
“…The mechanism(s) that underlie both the antineoplastic and adverse effects of these anticancer drugs are unproven, but may include 1) oxidative stress, including the formation of reactive oxygen species and/or cell membrane damage via lipid peroxidation; 2) intercalation into nucleic acids, causing suppression of DNA, RNA, and protein synthesis; 3) induction of DNA damage through interference with topoisomerase II; 4) disturbances of calcium balance and iron homeostasis in myocardial cells; 5) induction of apoptosis; 6) rise in cardiac histamine release; and 7) generation of toxic metabolites (Klugmann et al, 1986;Gewirtz, 1999;Hrdina et al, 2000;Minotti et al, 2004;Sim unek et al, 2009;Mordente et al, 2009;Sawyer et al, 2010). Ample evidence has been published both supporting and countering each of these proposed mechanisms of anthracycline-induced cellular damage; consequently, there is little consensus on the underlying causality of the cellular damage.…”
Section: Introductionmentioning
confidence: 99%